2018
DOI: 10.1111/icad.12317
|View full text |Cite
|
Sign up to set email alerts
|

Rediscovery of Brassicogethes salvan (Coleoptera: Nitidulidae, Meligethinae) in the southwestern Alps

Abstract: Brassicogethes salvan (Audisio et al. Insect Systematics and Evolution, 34, 121) is certainly among the most important and unexpected recent discoveries in the European beetle fauna. The species was initially described from a couple of unidentified specimens collected in 1912 on the Maritime Alps (NW Italy). Despite a long series of attempts to recollect the species at the type locality (Rovina Lake, Mount Argentera Massif, Cuneo Province, Piedmont, NW Italy) and several neighbouring areas of the SW Alps betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…As reported in our Meligethes revision [7], and in more recent papers [8][9][10] Despite the incomplete taxonomic and biogeographic coverage, the present morphological phylogenetic analysis and the thus far available molecular data seem to support at least the following conclusions: 1) Based on molecular evidence, the Meligethes complex of genera univocally represents a monophyletic lineage, including almost certainly three species-rich genera or subgenera (Meligethes s.str., Odonthogethes, and Brassicogethes), which are comparable in the number of inclusive species (32, 31 and 42 species, respectively). Other preliminary molecular data using mitochondrial and nuclear markers (COI, NADH, ITS2, PEPCK) [24,26], suggested that the genus Meligethinus Grouvelle (a small, mostly Oriental and Afrotropical genus including some 20 species associated as larvae with male in orescences of Arecaceae [1,46]) is placed as sister of this clade.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…As reported in our Meligethes revision [7], and in more recent papers [8][9][10] Despite the incomplete taxonomic and biogeographic coverage, the present morphological phylogenetic analysis and the thus far available molecular data seem to support at least the following conclusions: 1) Based on molecular evidence, the Meligethes complex of genera univocally represents a monophyletic lineage, including almost certainly three species-rich genera or subgenera (Meligethes s.str., Odonthogethes, and Brassicogethes), which are comparable in the number of inclusive species (32, 31 and 42 species, respectively). Other preliminary molecular data using mitochondrial and nuclear markers (COI, NADH, ITS2, PEPCK) [24,26], suggested that the genus Meligethinus Grouvelle (a small, mostly Oriental and Afrotropical genus including some 20 species associated as larvae with male in orescences of Arecaceae [1,46]) is placed as sister of this clade.…”
Section: Discussionsupporting
confidence: 75%
“…Meligethes, even as presently bounded [2] (Figs. 1A (a), (b)), is still a rather species-rich genus, consisting of more than 60 species predominantly occurring in the Eastern Palaearctic [7][8][9][10] (Fig. 1B-C; Table 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this taxon, the diverse subfamily Meligethinae comprises about 700 pollen-eating species described worldwide [ 1 – 4 ]. Recently, the classification of Meligethinae underwent numerous changes in light of both molecular and morphological evidence, restricting the concept to several genera, particularly in the case of the previously polyphyletic genus Meligethes Stephens, 1830 [ 2 , 5 , 6 ]. Meligethes , even as presently bounded [ 2 ] [Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The closely related and purported sister genus Brassicogethes Audisio & Cline, 2009 [Fig. 1 a (c), d], comprises instead some forty, mostly Western Palaearctic species, all associated with Brassicaceae [ 2 , 5 , 14 23 ], and a few species [e.g. B. aeneus (F.) and B. viridescens (F.)] represent economically important pests, massively attacking blossoms of oilseed rapes, broccoli, cauliflowers, and others.…”
Section: Introductionmentioning
confidence: 99%